The Holy Quran Words between the Primary and Secondary Significance: An Analytical Study - Shehata, Hussein; Abdullatif, Ali (Journal of Umm Al-Qura University for Language Sciences and Literature, 2023)
There was an apparent linguistic dispute about the pivotal significance of many language words in the specialized linguistic dictionaries. To know the semantic differences between these Quranic words, and the link between each word and its vocabulary network. The study followed the inductive analytical approach and came with an introduction and ten requirements. One of the most important findings of the study is that the number of roots that indicate a pivotal indication of the meaning of “return” in the Holy Qur’an is “nine” roots, which are, in order: aoba’, repentance, thawb, radd, oud, fa’, relapse, and nob. And that the meaning of the return has marginal connotations, and that there are semantic differences between the different linguistic roots that indicate the return in the Holy Qur’an. The study recommended the work of a comprehensive encyclopedia of the words of the Holy Qur’an that displays the eloquence of the pivotal significance and the peripheral significance related to it.